Investigation of Interfacial Shear Stresses, Shape Fixity, and Actuation Strain in Composites Incorporating Shape Memory Polymers and Shape Memory Alloys - Park, Jungkyu; Headings, Leon M.; Dapino, Marcelo J.; Baur, Jeffery W.; Tandon, Gyaneshwar P. (Frontiers in Materials, 2015)
Shape memory composites (SMCs) based on shape memory alloys (SMAs) and shape memory polymers (SMPs) allow many design possibilities due to their controllable temperature-dependent mechanical properties. The complementary characteristics of SMAs and SMPs can be utilized in systems with shape recovery created by the SMA and shape fixity provided by the SMP. In this research, three SMC operating regimes are identified and the behavior of SMC structures is analyzed by focusing on composite shape fixity and interfacial stresses. Analytical models show that SMPs can be used to adequately fix the shape of SMA actuators and springs. COMSOL finite element simulations are in agreement with analytical expressions for shape fixity and interfacial stresses. Analytical models are developed for an end-coupled linear SMP-SMA two-way actuator and the predicted strain is shown to be in good agreement with experimental test results.